MESIAS: a web-based platform rooted in ethical principles for evaluating trustworthiness in AI projects - Romani, Georgina; Avendaño, Cesar; Santisteban, José (Frontiers in Computer Science, 2025)
The accelerated growth of artificial intelligence (AI)-based projects has intensified the need for tools to assess their reliability, safety, and ethical alignment. In response to this challenge, the MESIAS initiative was developed. MESIAS is a web-based platform that provides a framework for evaluating AI systems through the lenses of ethical principles and international governance frameworks. The tool features a virtual assistant, adaptive forms, and a monitoring dashboard. The validation process comprised three steps: a preliminary investigation into operational efficiency, expert judgment validation with technological leaders, and a user satisfaction validation with 52 technology professionals. The operational assessment revealed a substantial 41.8% reduction in total assessment time and a 40% reduction in human resources required. Expert validation reflected a general acceptance of 85%. User validation revealed elevated satisfaction levels: 92% for usability, 94% for content, 91% for follow-up, and 95% for overall satisfaction. The study results indicate that the MESIAS strategy is a practical and effective approach to enhancing ethical governance in AI, particularly in public settings, fostering more responsible and informed decision-making processes.